Bibliometric analysis study on cognitive function in developmental coordination disorder from 2010 to 2022 - Ji, Zhiguang; Wang, Liyan; Cai, Ming; Lu, Le; Wang, Hongbiao (Frontiers in Psychology, 2022)
OBJECTIVE: To reveal the hot research on the cognitive function of the DCD population in recent years, predict the research frontier and development trend, and provide more perspectives for the study of the DCD population. METHODS: Using CiteSpace and VOSviewer software to draw charts, 362 pieces of literature about DCD and cognitive function in the Web of Science core collection database from 2010 to 2022 were visually analyzed. RESULTS AND CONCLUSION: Interest in the cognitive function of the DCD has been on the rise in the past ten years. Over 40 countries and regions, 117 institutions and 200 researchers have participated in the corresponding research, mainly in the United States, and their institutions have published more and highly influential results; the hot keywords are DCD, children, attention, working memory, performance, and ADHD, and the main research hot topics include functional performance, population, and cognitive psychology, etc.; the research directions include DCD”, “asperger syndrome, “memory”, “infant” and “clumsiness” , “Neurodevelopmental disorder”, “occupational therapy”, “preschool children”, “motor competence”, “model” and “online control”. Future research can focus on motor imagery, internal models, etc., with the help of more cognitive science and technology to reveal the cognitive function characteristics of DCD populations and to better formulate intervention plans.